The Ravens - Sundstol, Vidar, 1963- (Book collections on Project MUSE., 2015)
"It's been a long, dark time since a gruesome discovery drew U.S. Forest Service ranger Lance Hansen into a murder investigation that is now approaching a resolution--although not to his satisfaction. In fact, the mysteries have been multiplying and getting uncomfortably close to home. On the run after a hunting expedition with his brother, Andy, went awry, Lance is haunted by visions of Swamper Caribou, the Ojibwe medicine man whose death a century earlier remains unexplained. Willy Dupree, Lance's former father-in-law, has the ability to interpret dreams--and what he reveals may be key to understanding both deaths, past and present. Reluctantly taking on the role of detective, Lance uncovers troubling connections and grim secrets that will shake him to his very core. In the final installment of his award-winning Minnesota Trilogy, Norwegian crime writer Vidar Sundstol's affinity for the northern world of Lake Superior is on full display--as Lance's search takes him from the wilds of the Boundary Waters to outposts steeped in voyageur history and Ojibwe culture, from the streets of the Twin Cities to the gritty port of Duluth, to the sleepy tourist towns that dot the North Shore--and as the mysteries of love and nature, history and culture merge in a powerful conclusion."--